Peranan Guru PAI dalam Menanamkan Etika Berpakaian pada Siswi - Sri Juwita; Halimatussakdiah, Halimatussakdiah; Firmansyah, Firmansyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study is entitled the role of Islamic Religious Education teachers in instilling dress ethics to female .This study focuses on two problem formulations, namely how the dress ethics of female students and how the role of Islamic Religious Education teachers in instilling dress ethics to female students. The purpose of this study was to determine the dress ethics of female students and analyze the role of Islamic Religious Education teachers in instilling dress ethics to female students This study uses field research with a descriptive qualitative approach. Data collection techniques through observation, interviews, and documentation. Research informants consisted of Islamic Religious Education teachers and female students Data analysis techniques were carried out through reduction, data presentation, and drawing conclusions. The results of the study showed that the dress ethics of female students were quite good, with most female students covering their genitals, wearing neat and clean clothes, and not disturbing others. The role of Islamic Religious Education teachers as educators, advisors, and role models is very large in instilling dress ethics through checking uniforms, advice, and real examples. The disciplined and authoritative personality of teachers supports the success of coaching. The positive impact of this ethical dress coaching is seen in the increasing awareness of female students to maintain polite and neat clothing. Collaboration between teachers, schools, and female students is very important to strengthen the culture of dressing according to religious values in schools.